Analysis of energy demand by a 24-hour store - Rusowicz, Artur (International Conference “Environmental Engineering”, 2023)
The paper presents the balance of electricity consumption and fuel oil consumption of a medium-sized 24-hour store. Measurements of the electricity consumption of the various components of the balance were made for air conditioning, refrigeration, fast food, and especially for indoor and outdoor lighting. Their shares over the 12-month period of measurements were determined. Opportunities to reduce electricity consumption by changing the type of lighting of the facility were identified. Replacement of lighting reduced electricity consumption by 38535.8 kWh, which represented a total reduction of 21.2% in the store’s annual electricity consumption.